Analysis of relative humidity sensors at the WMO Radiosonde intercomparison experiment in Brazil - Sapucci, L. F.; Machado, LAT; da Silveira, R. B.; Fisch, G.; Monico, JFG (Amer Meteorological Soc, 2005)
The quality of the vertical distribution measurements of humidity in the atmosphere is very important in meteorology due to the crucial role that water vapor plays in the earth's energy budget. The radiosonde is the humidity measurement device that provides the best vertical resolution. Also, radiosondes are the operational devices that are used to measure the vertical profile of atmospheric water vapor. The World Meteorological Organization (WMO) has carried out several intercomparison experiments at different climatic zones in order to identify the differences between the available commercial sensors. This article presents the results of an experiment that was carried out in Brazil in 2001 in which major commercial radiosonde manufacturers [e.g., Graw Radiosondes GmbH & Co., KG (Germany); MODEM (France); InterMet Systems (United States); Sippican, Inc. (United States); and Vaisala (Finland)] were involved. One of the main goals of this experiment was to evaluate the performance of the different humidity sensors in a tropical region. This evaluation was performed for different atmospheric layers and distinct periods of the day. It also considers the computation of the integrated water vapor (IWV). The results showed that the humidity measurements achieved by the different sensors were quite similar in the low troposphere (the bias median value regarding the RS80 was around 1.8%) and were quite dispersed in the superior layers (the median rms regarding the RS80 was around 14.9%).